Variation in the risk of venous thromboembolism following colectomy - Humes, D.J.; Walker, A.J.; Blackwell, J.; Hunt, B.J.; West, Joe (John Wiley & Sons, Ltd, 2015)
Background: Guidelines recommend extended thromboprophylaxis following colectomy for malignant disease, but not for non-malignant disease. The aim of this study was to determine absolute and relative rates of venous thromboembolism (VTE) following colectomy by indication, admission type and time after surgery.